Gender Difference in the Association of Early- vs. Late-Onset Type 2 Diabetes with Non-Fatal Microvascular Disease in China: A Cross-sectional Study - Huo, Xiaoxu; Zhang, Junqing; Guo, Xiaohui; Lu, Juming; Li, Jing; Zhao, Wei; Ji, Linong; Yang, Xilin (Frontiers in Endocrinology, 2018)
Background: This study aimed to test whether early-onset (defined as <40 years of age) type 2 diabetes mellitus (T2DM) imparted different risks of microvascular disease to Chinese men and women. Methods: 222,537 Chinese patients with T2DM were recruited in 630 hospitals from 106 cities in 30 provinces of China in 2012 using a cross-sectional design. Logistic regression analysis was performed to obtain odds ratios (OR) of male versus female for diabetic retinopathy (DR) and diabetic nephropathy (DN). Additive interaction was used to test whether male gender and early-onset T2DM had interactive effects for DR and DN. Results: More men than women with T2DM had DN (4.5% vs. 3.0%, P<0.0001), DR (5.3% vs. 5.1%, P<0.0001) and microvascular disease (either DN or DR) (8.4% vs. 7.1%, P<0.0001). After adjustment for age and levels of hospitals, the effect sizes of early-onset T2DM and microvascular disease were higher in men than in women, with a 2.67(95%CI: 2.51-2.85) fold risk in men and a 2.53(95%CI: 2.35-2.72) fold risk in women. The risk effect sizes were greatly attenuated by further adjusting for diabetes durations and other traditional risk factors, with a 1.28 (95%CI: 1.19-1.37) fold risk in men and a 1.07 (95%CI: 0.99-1.16) fold risk in women. After adjustment for diabetes durations and other traditional risk factors, using women with late-onset T2DM as the reference, co-presence of early-onset and male gender significantly enhanced the ORs of either early-onset alone (1.10, 95%CI: 1.03-1.19) or male gender alone (0.96, 95%CI: 0.93-0.99) to 1.32 (95%CI: 1.24-1.41), with significant additive interaction. Kaplan Meier analysis showed that in early onset T2DM, DN developed 5 years earlier in men than in women. Conclusions: Early-onset T2DM increased more risk of micro-vascular complications in Chinese men than in women, most of increased risks being attributable to longer diabetes durations.